The psychometric properties of the barriers to insulin treatment questionnaire in Chinese patients with type 2 diabetes mellitus using insulin - Ma, Min; Ma, Xiquan; Chang, Jingzhi; Yin, Feiyan; Ma, Sha; Zhang, Yuan; Shi, Zhidao (Frontiers in Endocrinology, 2023)
Aim: Translate the Barriers to Insulin Treatment Questionnaire (BIT) into Chinese and test its psychometric properties in middle-aged and elderly Type 2 diabetes (T2D) patients using insulin in the Han people of urban China.We established the BIT in Chinese (BIT-C). We selected 296 patients with T2D for testing BIT-C's reliability and validity, of which 120 patients were retested four weeks later. Another 200 patients with T2D were selected for performing Confirmatory Factor Analysis (CFA).The final BIT-C consisted of 11 items (BIT-C-11) and four factors. The explained variances of BIT-C-11 and its four factors were 90.153%, 51.308%, 18.810%, 10.863%, and 9.173%. CFA validated that the four-factor model fit with the data of BIT-C-11. Standardized factor loadings ranged between 0.77 and 0.90. The Cronbach's alpha coefficient of BIT-C-11 and its four factors were 0.903, 0.952, 0.927, 0.938, and 0.917. Correlation analysis was performed between BIT-C-11 and General Adherence Scale in Chinese (GAS-C) to calculate the criterion-related validity (r=0.598 p< 0.001). The correlation coefficient r of the BIT-C-11's test-retest reliability was 0.810 (p< 0.001).BIT-C-11 has good reliability and validity. It can be used for psychological resistance to insulin therapy studies of middle-aged and elderly patients with T2D using insulin in the Han people of Chinese cities.